2006
DOI: 10.1042/cs20050255
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/Rho-kinase in erectile tissue: mechanisms of disease and therapeutic insights

Abstract: Penile erection is a complicated event involving the regulation of corpus cavernosal smooth muscle tone. Recently, the small monomeric G-protein RhoA and its downstream effector Rho-kinase have been proposed to be important players for mediating vasoconstriction in the penis. RhoA/Rho-kinase increases MLC (myosin light chain) phosphorylation through inhibition of MLCP (MLC phosphatase) thereby increasing Ca2+ sensitivity. This review will outline the RhoA/Rho-kinase signalling pathway, including the upstream r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 150 publications
1
52
0
Order By: Relevance
“…These results may provide clues for a better understanding of the molecular mechanisms of Ang II in apoptosis and fibrosis in the corpus cavernosum and severe CVOD, and of the critical role of Ang II in functional and morphological modification in the cavernous tissue of diabetic rats through Smad- and non-Smad-related signaling pathways. Furthermore, considering the fact that Rho/ROCK plays a pivotal role in diabetic ED by inducing cavernosal fibrosis [45] and increasing smooth muscle tone in the corpus cavernosum [46], Rho/ROCK may also be involved in mediating Ang II-induced diabetes-associated ED. Further studies are needed to clarify this relationship and whether combined inhibition of both signaling pathways could improve diabetes-induced cavernosal fibrosis and CVOD.…”
Section: Discussionmentioning
confidence: 99%
“…These results may provide clues for a better understanding of the molecular mechanisms of Ang II in apoptosis and fibrosis in the corpus cavernosum and severe CVOD, and of the critical role of Ang II in functional and morphological modification in the cavernous tissue of diabetic rats through Smad- and non-Smad-related signaling pathways. Furthermore, considering the fact that Rho/ROCK plays a pivotal role in diabetic ED by inducing cavernosal fibrosis [45] and increasing smooth muscle tone in the corpus cavernosum [46], Rho/ROCK may also be involved in mediating Ang II-induced diabetes-associated ED. Further studies are needed to clarify this relationship and whether combined inhibition of both signaling pathways could improve diabetes-induced cavernosal fibrosis and CVOD.…”
Section: Discussionmentioning
confidence: 99%
“…Chitaley et al [8] reported that Rho-kinase antagonism stimulated rat penile erection independently of nitric oxide (NO) and showed potential alternative therapeutic options to treat ED. In fact, recently published literature has suggested that elevated RhoA/Rhokinase activity contributes to the pathogenesis of ED in conditions such as diabetes, aging, and hypogonadism [9]. Vignozzi et al [10] found that overexpression of RhoA/ Rho-kinase signalling contributed to diabetes-related ED and that treating hypogonadism-associated diabetes could improve the erectile function by normalizing the RhoA/Rhokinase pathway upregulation.…”
Section: Rhoa/rho-associated Kinase Pathwaymentioning
confidence: 98%
“…Within this perception, pharmacological blockage of AT 1 receptor/Ang-II actions through the use of ACE inhibitors and AT 1 receptor blockers, along with the use of oxidase inhibitors, anti fibrotic and Rho-Kinase inhibitors, have been reported to have positive effects on erections (Decaluwe, Pauwels, Verpoest, & Van de Voorde, 2011;Doumas & Douma, 2006;Fraga-Silva, Montecucco, Mach, Santos, & Stergiopulos, 2013;Jin & Burnett, 2006;Jin, Lagoda, Leite, Webb, & Burnett, 2008).…”
Section: Organic Modelsmentioning
confidence: 98%